Penilaian Kesehatan Pohon Pada Jalur Hijau Di Kota Palangka Raya Kalimantan Tengah : Tree Health Assessment on the Green Line in the City of Palangka Raya, Central Kalimantan - Desliana Saragih; Wahyudi Wahyudi; Patricia Erosa Putir (HUTAN TROPIKA, 2022)
This study aims to determine the level of tree health, determine the form of pest and disease attacks including damage caused by disturbance or human activities and make recommendations for tree species to be planted on the Green Line, Palangka Raya, Central Kalimantan. The method used is Forest Health Monitoring (FHM) through grouping the type and level of damage to each individual tree. The results showed that the number of trees found at the study site amounted to 301 individuals from 24 tree species. Analysis of the Health Level of Trees based on the value of the Tree Damage Level Index (TDLI) obtained the category of severe damage level of 45 trees or 15%, light damage level of 97 trees or 33%, and moderate damage level of 78 trees or 26% while healthy trees have total 78 trees or 26%. Based on the level of tree health, the types of trees suitable for planting in the green lane, Palangka Raya City are trembesi (Samanea saman (Jacq.) Merr.), Angsana (Pterocarpus indicus Willd.), and Ketapang (Terminalia catappa H. Perrier,). Kata kunci (Keywords): Green line, tree health level, trembesi, angsana, ketapang.